Recommended Contraindications for the Use of Non-Medical WB-Electromyostimulation - Kemmler, Wolfgang; Weißenfels, Anja; Willert, Sebastian; Fröhlich, M.; Ludwig, O.; Berger, J.; Zart, S.; Becker, S.; Backfisch, M.; Kleinöder, H.; Dörmann, U.; Wirtz, N.; et al. (Deutsche Zeitschrift für Sportmedizin, 2019)
Rare but regularly recurring complications are leading to ongoing regulation of the commercial, non-medical whole-body electromyostimulation (WB-EMS) market. In addition to the revised German Radiation Protection Statutes (NiSV), the “Deutsche Industrie Norm” (DIN) 33961-5 was recently published with safety policies for WB-EMS application, anchoring both relative and absolute contraindications for WB-EMS for the first time. The purpose of this article is to justify the rationale of contraindications in a commercial setting and to support their consistent application. › While the relative contraindications appear plausible and uncritical, absolute contraindications for WB-EMS are much more debatable. In fact, some absolute contraindications (e.g. diabetes mellitus) could be safely addressed by WB-EMS at least after careful medical anamnesis and competent, close supervision. However, this requires sound knowledge of WB-EMS on the part of physicians and instructors, low user-trainer ratios and prompt medical care in an emergency. › However, considering the multitude of different settings of commercial WB-EMS, in extreme cases with hardly supervised, only video-guided WB-EMS sessions, the necessary accurateness and expertise for safe WB-EMS is not always guaranteed. That there is no mandatory licensing of WB-EMS instructors, the key players in WB-EMS, underscores the concern. › Whilst acknowledging the multitude of high-quality suppliers, it is advised that the commercial, non-medical WB-EMS sector as a whole to be wary of indications with significantly increased complication potential. Lastly, the mandatory acceptance of the contraindications listed in DIN 33961-5 might be considered as an inevitable step towards preventing overregulation by official authorities.
CRIS-Team Scopus Importer:2020-02-21
Keywords: Commercial Application; DIN 33961-5; Guideline; Whole-Body Electromyostimulation